Sex Differences in Acute Complications of Cardiac Implantable Electronic Devices: Implications for Patient Safety. Issue 2 (22nd January 2019) - Moore, Katherine; Ganesan, Anand; Labrosciano, Clementine; Heddle, William; McGavigan, Andrew; Hossain, Sadia; Horton, Dennis; Hariharaputhiran, Saranya; Ranasinghe, Isuru
Abstract : Background: To date, limited population‐level studies have examined the impact of sex on the acute complications of cardiac implantable electronic devices (CIED), including permanent pacemakers, implantable cardioverter defibrillators, and cardiac resynchronization therapy devices. Methods and Results: We studied all patients aged >18 years from 2010 to 2015 who were a resident of Australia or New Zealand, undergoing a new permanent pacemaker, implantable cardioverter defibrillator, or cardiac resynchronization therapy implant. Standardized variables were collected including patient demographic characteristics, primary and secondary diagnoses, procedures performed and discharge status. Diagnoses and procedures were coded as per the International Classification of Diseases, Tenth Revision ( ICD‐10 ) and the Australian Classification of Health Interventions. The primary end point was the incidence of major CIED‐related complications in‐hospital or within 90 days of discharge, with the effect of sex evaluated using multiple logistic regression. A total of 81 304 new CIED (61 658 permanent pacemakers, 12 097 implantable cardioverter defibrillators, 7574 cardiac resynchronization therapy) implants were included (38% women). Overall, 8.5% of women and 8.0% of men experienced a CIED complication ( P =0.008). Differences between women and men remained significant after adjustment for age, procedural acuity, and comorbidities (odds ratio 1.10, 95% CI: 1.04–1.16, P <0.001). Differences in CIED complication rates were primarily driven by excess rate of in‐hospital pleural drainage (1.2% women versus 0.6% men, P <0.001; adjusted odds ratio 1.86, 95% CI: 1.59–2.17, P <0.001) and pericardial drainage (0.3% women versus 0.1% men, P <0.001; adjusted odds ratio 2.17, 95% CI: 1.48–3.18, P <0.001). Conclusions: Women are at higher risk of acute CIED complications. Improvements in implant technique and technologies are required to minimize the risk of implant‐related complications in women.